(untitled) (Research, Society and Development, 2025)
Splenic nodular lesions in dogs pose significant diagnostic challenges, especially due to overlaps between benign and malignant processes. This report describes a case of splenic lymphoid nodular hyperplasia in an elderly mixed-breed dog, focusing on clinical, pathological, and therapeutic aspects. A descriptive study was conducted using clinical examinations, medical records, imaging, and histopathology. The patient presented with abdominal distension and spontaneous hemoperitoneum, which was attributed to a ruptured splenic hematoma. Splenectomy was performed, and histopathology revealed lymphoid hyperplasia with associated hemorrhage and necrosis, with no malignancy. Hematological findings included regenerative anemia, consumption thrombocytopenia, and neutrophilic leukocytosis. Biochemistry showed azotemia and mild liver enzyme elevation. Histopathological examination was key for definitive diagnosis, as imaging and cytology were inconclusive regarding the lesion’s nature. Surgical removal of the spleen led to clinical stabilization. It is concluded that, although benign, nodular lymphoid hyperplasia can result in severe clinical outcomes. Complete splenectomy and thorough histopathological analysis are essential for accurate diagnosis and appropriate treatment planning.